PENGGUNAAN TEKNOLOGI PEMBELAJARAN PAI BERBASIS GAYA BELAJAR SISWA DI MTS DARUL HIKMAH - Realita Realita; Irda Muzfira (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The development of an increasingly advanced era now, requires all levels of institutions to always be updated in updating the system in all fields, both from the layers of government, offices, trade, business and even education. Because it is expected to always update the system it is said to be able to compensate for the flow of modernization like the current era. With the existence of various new technologies, it is hoped that all communities will be able to master them so that they can make it easier to carry out any activity. Likewise with education especially the learning system, it is expected that all people who interact with each other in a school institution must be able to utilize and use technology to the fullest so that it can help facilitate interaction between educators and students in delivering a material when learning takes place. And educators and educators can compete fairly in the current era of modernization. That is the initial description that will be explained in this article.